Variable Number Tandem Repeats in the Mitochondrial DNA of Lentinula edodes - Kim, Sinil (Genes (Basel), 2019)
Variable number tandem repeats (VNTRs) in mitochondrial DNA (mtDNA) of Lentinula edodes are of interest for their role in mtDNA variation and their application as genetic marker. Sequence analysis of three L. edodes mtDNAs revealed the presence of VNTRs of two categories. Type I VNTRs consist of two types of repeat units in a symmetric distribution, whereas Type II VNTRs contain tandemly arrayed repeats of 7- or 17-bp DNA sequences. The number of repeat units was variable depending on the mtDNA of different strains. Using the variations in VNTRs as a mitochondrial marker and the A mating type as a nuclear type marker, we demonstrated that one of the two nuclei in the donor dikaryon preferentially enters into the monokaryotic cytoplasm to establish a new dikaryon which still retains the mitochondria of the monokaryon in the individual mating. Interestingly, we found 6 VNTRs with newly added repeat units from the 22 mates, indicating that elongation of VNTRs occurs during replication of mtDNA. This, together with comparative analysis of the repeating pattern, enables us to propose a mechanistic model that explains the elongation of Type I VNTRs through reciprocal incorporation of basic repeat units, 5’-TCCCTTTAGGG-3’ and its complementary sequence (5’-CCCTAAAGGGA-3’).